A comparison of spherical and cylindrical microparticles composed of nanoparticles for pulmonary application. Issue 1 (2nd January 2019) - Torge, Afra; Pavone, Greta; Jurisic, Marijas; Lima-Engelmann, Karola; Schneider, Marc
Abstract: Nano-embedded microparticles represent promising carrier systems to tackle the challenges of nanoparticle delivery into the lungs by inhalation. While spray drying is widely used for the incorporation of nanoparticles into microparticles, the template-assisted technique is a novel method to prepare aspherical, cylindrical microparticles composed of nanoparticles. In this work, both techniques were applied to produce both spherical and cylindrical nano-embedded microparticles. For both geometries particles consisting of gelatin nanoparticles, mannitol and leucine were prepared in three different sizes each. Cylindrical microparticles could be prepared with defined dimensions and narrow size distributions, allowing to target a wide range of aerodynamic diameters. The size of spherical microparticles was influenced by the spraying feed concentration, yielding only small differences in geometric and aerodynamic diameters and broad particle size distributions. Regarding the redispersibility of the nano-embedded microparticles, spherical particles showed better disintegration behavior and higher nanoparticle release in comparison to cylindrical particles upon contact with water. The template-assisted technique yielded higher nanoparticle content in contrast to spray drying. In summary, cylindrical particles represent a promising drug delivery system with high potential for later application. However, further improvements in the preparation method are required to enable higher yields and a possible later scale-up. Copyright © 2018 American Association for Aerosol Research